Effect of Oxygen and Initiator Solubility on Admicellar Polymerization of Styrene on Silica Surfaces. (15th March 2017) - Cheah, Pohlee; Bhikha, Caitlin N.; O'Haver, John H.; Smith, Adam E.
Abstract : Although admicellar polymerization has been termed the surface analog of emulsion polymerization, previous reports utilizing free radical-initiated admicellar polymerization relied on high levels of the free radical initiator when compared to emulsion polymerization, likely due to the presence of oxygen in the reported admicellar polymerization systems. Admicellar polymerizations of styrene on the surface of precipitated silica initiated by either a water-soluble or a water-insoluble initiator were studied to determine the effect of dissolved oxygen and free radical initiator solubility on the kinetics, yield, and molecular weight of the polymer formed. Results show that the presence of oxygen reduces the polymer yield and limits molecular weight. The solubility of the initiator also affected the polymer formed in the admicellar polymerization of styrene. While monomer conversions and polymer yield were similar, the molecular weights of polymerizations initiated by a water-soluble initiator were higher than comparable polymerizations initiated by a water-insoluble initiator.